Méthodes biographiques et théologie pratique - Grieu, Étienne (2009)
Interest in life stories of ordinary people is becoming more and more widespread since the XIX century (in fields like literature, history, sociology, arts, and so on). Does this matter interest in any way theology? The author, after introducing briefly the methods using life stories in sociology and making reference to Paul Ricoeur, proposes three possible ways of using those stories in theology. In fact, such use can help us: firstly, to understand people that we meet at a pastoral level; secondly, to re-examine a classical theological question, taking into account the experience of Christians; thirdly, to contribute to the formation of active participants in the Church. The author insists particularly on the second aspect, by referring to his doctoral thesis. He proposes a way of proceeding that consists of going back and forth between commentaries of the Bible and commentaries of life stories, around a theological question.